In-situ monitoring method for optical and / or thermal degradation mechanism of organic-inorganic hybrid perovskite thin film

By combining in situ Raman spectroscopy, PL and XRD technologies, monitoring the light and/or thermal degradation process of perovskite films, the problem of insufficient stability of perovskite solar cells is solved, and the in-situ monitoring of the degradation mechanism and the research strategy of film quality improvement is realized.

CN119574530APending Publication Date: 2025-03-07CHANGCHUN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411744791.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Perovskite solar cells are inadequately stable and are susceptible to factors such as water, heat, light, and electrical bias, causing battery performance to deteriorate, hindering their commercialization process.

Method used

In situ Raman spectroscopy technology is used in combination with PL and XRD to monitor the light and/or thermal degradation process of organic-inorganic hybrid perovskite films. By collecting Raman data and XRD and PL spectral data, the transformation of the phases and the interaction between ions and vacant positions during the film degradation process are analyzed.

Benefits of technology

In-situ non-destructive monitoring of the light and/or thermal degradation mechanism of perovskite thin films is realized, revealing the relationship between phase changes and battery performance during the degradation process, and providing a research strategy and theoretical basis for improving the quality and performance of the thin film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119574530A_ABST
    Figure CN119574530A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ monitoring method for an optical and / or thermal degradation mechanism of an organic-inorganic hybrid perovskite thin film. The in-situ monitoring method comprises the following steps: carrying out thermal degradation and / or light degradation on an organic-inorganic hybrid perovskite film, and collecting Raman data and XRD diffraction peak data of the organic-inorganic hybrid perovskite film in the thermal degradation process by utilizing a Raman and XRD coupling technology; and / or collecting Raman data and PL spectrum data of the organic-inorganic hybrid perovskite thin film in the photodegradation process by using a Raman and PL spectrum technology; and the obtained data are analyzed and processed, so that in-situ nondestructive monitoring is realized. According to the method, the optical and / or thermal degradation mechanism of the perovskite thin film is explored through the combination of the Raman spectrum, the PL and the XRD, an in-situ technology for researching the degradation mechanism of the perovskite thin film and evaluating the quality of the perovskite thin film is established, and the technology provides a research strategy and a theoretical basis for monitoring the quality of the perovskite thin film and improving the photovoltaic performance of the perovskite thin film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic-inorganic hybrid perovskite thin films, and relates to an in-situ monitoring method for the light and / or thermal degradation mechanism of an organic-inorganic hybrid perovskite thin film. Background Art

[0002] In the past few years, perovskite materials have attracted widespread attention due to their superior photovoltaic performance, especially their application in the field of photovoltaic (PV) cells has been widely studied. The combination of high efficiency, low cost and additional (non-photovoltaic) applications provides great potential for the commercialization of perovskite solar cells. Nowadays, the photoelectric conversion efficiency of organic-inorganic hybrid perovskite solar cells (PSCs) has reached more than 25%, and they have gained amazing attention and success due to their ease of manufacture and low cost, which makes them a real commercial competitor to traditional silicon technology. However, perovskite solar cells still have problems such as insufficient stability and easy degradation. Achieving long-term stability of perovskite solar cells can be said to be the most important challenge required for widespread commercialization. Since perovskite solar cells are easily affected by multiple factors such as water, heat, light, and electrical bias, the performance of the cells is degraded, which greatly hinders their commercialization process. Therefore, it is urgent to provide an in situ monitoring technology for light and / or thermal degradation in organic-inorganic hybrid perovskite films. In situ Raman spectroscopy is a non-destructive in situ analytical technique with high detection sensitivity. Raman spectroscopy is expected to play its advantages in the in-situ characterization of perovskite thin film materials and photovoltaic devices. It can be used to detect subtle differences between different samples in the film or device and between different parts of the same sample, thereby helping to understand the degradation process and mechanism of perovskite materials and providing new strategies for improving the quality and performance of the film. Summary of the invention

[0003] The main purpose of the present invention is to provide an in-situ monitoring method for the photo- and / or thermal degradation mechanism of an organic-inorganic hybrid perovskite film to overcome the deficiencies of the prior art.

[0004] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0005] The embodiment of the present invention provides an in-situ monitoring method for the photo- and / or thermal degradation mechanism of an organic-inorganic hybrid perovskite film, which comprises:

[0006] The organic-inorganic hybrid perovskite film is subjected to thermal degradation and / or photodegradation, and Raman data and XRD diffraction peak data of the organic-inorganic hybrid perovskite film during the thermal degradation process are collected using Raman and XRD combined technology; and / or, Raman data and PL spectrum data of the organic-inorganic hybrid perovskite film during the photodegradation process are collected using Raman and PL spectrum technology;

[0007] The acquired data are analyzed and processed to realize in-situ nondestructive monitoring of the photo and / or thermal degradation of organic-inorganic hybrid perovskite films.

[0008] The present invention provides a technical means of combining in-situ Raman spectroscopy with PL and with XRD to achieve in-situ monitoring of the light and / or thermal degradation mechanism of perovskite films, and establish the connection between the phase transformation during the degradation of perovskite films and the interaction between ions and vacancies and the change in battery performance.

[0009] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention provides a technical means of combining in-situ Raman spectroscopy with PL and with XRD, which successfully realizes the monitoring of the light and / or thermal degradation mechanism of organic-inorganic hybrid perovskite films, filling the gap in the in-situ characterization technology of perovskite films; through the combination of Raman spectroscopy with PL and XRD, an in-situ technology for studying the degradation mechanism of perovskite films and evaluating the quality of perovskite films is established, which provides a research strategy and theoretical basis for perovskite film quality monitoring and photovoltaic performance improvement. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0011] Figure 1a-Figure 1c It is the Raman spectrum of the FACsPbI3 perovskite film in Example 1 of the present invention under different irradiation times of a xenon lamp;

[0012] Figure 2a-2c It is the PL spectrum of the FACsPbI3 perovskite film in Example 1 of the present invention under different irradiation times of a xenon lamp;

[0013] Figure 3a-3c is the Raman spectrum of the FAMAPbI3 perovskite film at different temperatures in Example 1 of the present invention;

[0014] Figure 4 is the XRD spectrum of the FAMAPbI3 perovskite film at different temperatures in Example 1 of the present invention;

[0015] Figure 5a-5f It is the Raman spectrum of the FACsPbI3 perovskite film in Example 2 of the present invention under different irradiation times of a xenon lamp;

[0016] Figure 6a-6fIt is the PL spectrum of the FACsPbI3 perovskite film in Example 2 of the present invention under different irradiation times of a xenon lamp;

[0017] Figure 7a-7c is the Raman spectrum of the FAMAPbI3 perovskite film at different temperatures in Example 2 of the present invention;

[0018] Figure 8a-8b 1 is the XRD spectrum of the FAMAPbI3 perovskite film at different temperatures in Example 2 of the present invention. DETAILED DESCRIPTION

[0019] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. It mainly provides a technical means for monitoring the light (xenon lamp, laser degradation) and / or thermal degradation mechanism of perovskite films by combining in-situ Raman spectroscopy technology with PL and XRD, so as to explore the phase transformation during the degradation process and the interaction between ions and vacancies, and decouple the photothermal mechanism during the film degradation process.

[0020] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Specifically, as one aspect of the technical solution of the present invention, an in-situ monitoring method of the light and / or thermal degradation mechanism of an organic-inorganic hybrid perovskite film involves:

[0022] The organic-inorganic hybrid perovskite film is subjected to thermal degradation and / or photodegradation, and Raman data and XRD diffraction peak data of the organic-inorganic hybrid perovskite film during the thermal degradation process are collected using Raman and XRD combined technology; and / or, Raman data and PL spectrum data of the organic-inorganic hybrid perovskite film during the photodegradation process are collected using Raman and PL spectrum technology;

[0023] The acquired data are analyzed and processed to realize in-situ nondestructive monitoring of the photo and / or thermal degradation of organic-inorganic hybrid perovskite films.

[0024] In some preferred embodiments, the in situ monitoring method specifically comprises:

[0025] The organic-inorganic hybrid perovskite film was heat treated by a hot stage, and the Raman data and XRD diffraction peak data of the organic-inorganic hybrid perovskite film at different temperatures were collected by using Raman and XRD combined technology;

[0026] The obtained Raman data and XRD diffraction peak data are analyzed and processed to clarify the phase changes, the interaction between ions and vacancies and their changing laws during the thermal degradation of organic-inorganic hybrid perovskite films.

[0027] Furthermore, Raman data and XRD diffraction peak data of the organic-inorganic hybrid perovskite film at at least three different temperatures between 25°C and 400°C are collected.

[0028] Furthermore, the time interval for collecting data at different temperature points is more than 20 minutes.

[0029] Furthermore, Raman data and XRD diffraction peak data of the organic-inorganic hybrid perovskite film at at least 20 different temperatures between 25°C and 400°C are collected.

[0030] Furthermore, the organic-inorganic hybrid perovskite film may experience changes in its crystal structure during thermal degradation.

[0031] Furthermore, when the organic-inorganic hybrid perovskite film is a FAMAPbI3 perovskite film, the FAMAPbI3 perovskite structure is destroyed during the thermal degradation process, and MAI and FAI are released from the structure in sequence, so that the main component of the degradation product is PbI2; then PbI2 decomposes as the temperature rises, I- is released from the structure in the form of iodine, and the Pb remaining in the structure combines with O2 in the air to form PbO x Remain on the FTO surface.

[0032] In some preferred embodiments, the in situ monitoring method specifically comprises:

[0033] The organic-inorganic hybrid perovskite film is irradiated with a xenon lamp or laser to simulate photodegradation, and the Raman data and PL spectrum data of the organic-inorganic hybrid perovskite film under different illumination times are collected using Raman and PL spectrum techniques;

[0034] The obtained Raman data and PL spectrum data are analyzed and processed to clarify the phase changes, the interaction between ions and vacancies and their changing laws during the photodegradation of organic-inorganic hybrid perovskite films.

[0035] Furthermore, Raman data and PL spectrum data of at least 3 days from the start of irradiation of the organic-inorganic hybrid perovskite film to the 11th day are collected; for example: the start of irradiation, the 5th day, and the 11th day are selected.

[0036] Furthermore, Raman data and PL spectrum data are collected for at least 6 days from the start of irradiation of the organic-inorganic hybrid perovskite film to the 11th day, at least 5 time points per day.

[0037] Furthermore, the time interval for collecting light is generally more than 2 days.

[0038] Furthermore, when the organic-inorganic hybrid perovskite film is a FACsPbI3 perovskite film, during the photodegradation process, + Will first with PbI6 4- The interaction forms FAI, which is then completely released from the film, while CsPbI3 is formed in the film during the photodegradation process.

[0039] Furthermore, the wavelength of the laser is selected from 532nm, 633nm, 785nm or 1064nm.

[0040] In some preferred embodiments, the organic-inorganic hybrid perovskite film includes a FACsPbI3 perovskite film and / or a FAMAPbI3 perovskite film.

[0041] Furthermore, the preparation of the FACsPbI3 and FAMAPbI3 perovskite films comprises the following steps:

[0042] (1) Prepare FACsPbI3 and FAMAPbI3 perovskite precursor solutions respectively

[0043] (2) FACsPbI3 and FAMAPbI3 perovskite precursor solutions were respectively spin-coated on the FTO substrate by a one-step spin coating method. After hot stage annealing, FACsPbI3 and FAMAPbI3 perovskite films were obtained.

[0044] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0045] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0046] Example 1

[0047] 1. Preparation of perovskite thin films

[0048] (1) The newly purchased FTO was ultrasonically cleaned in acetone, isopropanol, methanol, and ethanol for 20 min.

[0049] (2) Place the cleaned FTO in a UV-ozone cleaning machine for 15 minutes to eliminate the interference of organic solvents on film formation.

[0050] (3) Prepare 1 M concentration of FACsPbI3 and FAMAPbI3 perovskite precursor solutions respectively, use a pipette to measure 50 μL and spin-coat them onto the FTO substrate, then place it on a hot plate for annealing at 100 °C for 10 min to obtain FACsPbI3 and FAMAPbI3 perovskite films.

[0051] 2. In situ Raman technology combined with PL to monitor the photodegradation mechanism of FACsPbI3 and FAMAPbI3 perovskite films

[0052] The FACsPbI3 and FAMAPbI3 perovskite films were irradiated with a xenon lamp to simulate the photodegradation under sunlight, and the FACsPbI3 and FAMAPbI3 perovskite films were irradiated with different laser powers (532nm) for a long time to simulate the laser degradation. In-situ Raman spectroscopy was used to monitor the Raman spectral changes of the perovskite film as it degraded under different irradiation times of the xenon lamp and laser, as well as the Raman spectral changes of the perovskite film under different laser powers, and PL was used for characterization.

[0053] Figure 1a-Figure 1c In situ Raman monitoring of the photodegradation process of FACsPbI3 perovskite film under xenon lamp. It can be observed from the figure that when the fresh FACsPbI3 perovskite film is irradiated with 100% laser, a 64.0 cm -1 、91.8cm -1 The Raman peak at 122.9 cm -1 、142.8cm -1 、281.0cm -1 The Raman peaks at 122.9 cm and 127.9 cm are the laser degradation products, which can be attributed to Pb3O4 (122.9 cm -1 ) and PbO(142.8cm -1 、281.0cm -1 ). After irradiating it under a xenon lamp for 5 days, the film gradually changed from black to brown. The Raman spectrum was collected and the 64.0 cm -1 、91.8cm -1 The Raman peak position at the bottom of the perovskite was slightly shifted, and no obvious difference was found in the other peaks, which indicates that with continuous xenon lamp irradiation, the Cs + Will migrate due to the influence of light intensity, PbI6 4- The octahedral cage is gradually destroyed, FA + With the decomposed I - The interaction forms FAI, which is unstable and therefore released from the perovskite. After 11 days of xenon lamp irradiation, the film gradually changes from light brown to light yellow. -1 、94.6cm -1A Raman peak can be observed at 352.6 cm -1 、561.8cm -1 、629.5cm -1 、1100.9cm -1 The characteristic peaks of FTO can be observed at the bottom, indicating that after 11 days of xenon lamp irradiation, the organic cation FA + It has been completely released from the perovskite structure, so the Raman peak of the substrate FTO appears. -1 、94.6cm -1 The Raman peak of the film may be caused by the presence of CsPbI3 in the film. To verify this result, PL tests were performed on the newly prepared FACsPbI3 perovskite film, the film irradiated under a xenon lamp for 5 days, and the film irradiated under a xenon lamp for 11 days. Figure 2a-2c shown.

[0054] Depend on Figure 2a-2c It can be seen that the PL of the newly prepared FACsPbI3 perovskite film is around 793nm. After 5 days of continuous irradiation with a xenon lamp, the PL of the substance was observed to gradually blue-shift. After 11 days of irradiation with a xenon lamp, the PL of the substance was observed to stabilize at around 699nm. According to the literature, this peak is the characteristic PL peak of CsPbI3. Combined with the previous Raman spectrum, it can be further proved that the inference of the degradation product is accurate, thus clarifying that the photodegradation mechanism of FACsPbI3 perovskite film under 532nm laser is that as the laser power increases, the perovskite is degraded into PbO x ; The photodegradation mechanism under xenon lamp is that as the illumination time increases, perovskite degrades into CsPbI3.

[0055] 3. In-situ Raman technology combined with XRD to monitor the thermal degradation mechanism of FACsPbI3 and FAMAPbI3 perovskite films

[0056] In-situ Raman was used to collect the Raman spectra of the newly prepared FACsPbI3 and FAMAPbI3 perovskite films at different temperatures, and XRD was used to characterize the FACsPbI3 and FAMAPbI3 perovskite films at different temperatures. The following figures are the Raman spectra of the FAMAPbI3 perovskite film at different temperatures measured at 1% laser power, and the XRD measured at room temperature, 225°C, and 380°C. Figure 3a-3c shown.

[0057] from Figure 3a-3c It can be observed that when the temperature rises from room temperature to 120 °C, the Raman peak (64.2 cm -1 、93.8cm -1) has not changed and is still in the perovskite phase. From 150℃, the PbI2 peak gradually appears. When the temperature rises to 170℃, the peak at 73.6cm -1 、93.8cm -1 、107.1cm -1 The Raman peak appears, which is very similar to the characteristic peak of PbI2. Therefore, it can be proved that the FAMAPbI3 perovskite film has begun to degrade with the increase of temperature, and its degradation product is PbI2. When the temperature rises to 210℃, it can be observed from the figure that the Raman spectrum of the film is basically consistent with the characteristic peak of PbI2, and the crystallinity is getting better and better. However, due to the presence of 62.0cm -1 The Raman peaks of the perovskite film indicate that the perovskite film is degraded to PbI2 over a large area, but there is still a part of the FAMAPbI3 perovskite structure. When the temperature rises to 355℃, the characteristic peak of lead iodide disappears and a new Raman peak appears; when the temperature rises to 380℃, the characteristic peak at 140.4cm -1 A Raman peak appeared, which may be the characteristic peak of PbO or polyiodide ion; then the PbO diffraction peak was observed in the variable temperature XRD data, so it was inferred that the 140.0cm -1 It is PbO instead of polyiodide ions. Here, XRD and Raman spectroscopy are combined to complement and verify each other. The combination of the two can give a clear product identification result.

[0058] The composition of the perovskite films at room temperature, 225°C, and 380°C were characterized by XRD, and compared with the XRD diffraction peaks of the raw materials, such as Figure 4 As shown in the figure, it can be observed that at 225°C, the FAMAPbI3 perovskite film has characteristic diffraction peaks of PbI2 at 11.34°, 12.59°, 38.54°, and 52.23°, and the signal of the perovskite diffraction peak disappears, indicating that the perovskite has basically degraded into PbI2 at this time. At 380°C, the FAMAPbI3 perovskite film has PbO at 28.57°, 29.45°, and 30.51°. x The characteristic diffraction peaks of PbI2 indicate that the temperature causes further degradation of PbI2 and combines with oxygen in the air to form PbO x This is completely consistent with the spectral characteristics obtained by in-situ Raman monitoring of perovskite films. It can be determined that the thermal degradation mechanism of perovskite films is that as the temperature increases, perovskite first degrades to PbI2 and then to PbO x .

[0059] Example 2

[0060] 1. The preparation of the perovskite film is the same as that in Example 1.

[0061] 2. In situ Raman technology combined with PL to monitor the photodegradation mechanism of FACsPbI3 and FAMAPbI3 perovskite films

[0062] The FACsPbI3 and FAMAPbI3 perovskite films were irradiated with a xenon lamp to simulate the photodegradation under sunlight, and the FACsPbI3 and FAMAPbI3 perovskite films were irradiated for a long time with different laser powers (532nm) to simulate laser degradation. In-situ Raman spectroscopy was used to monitor the Raman spectral changes of the perovskite film as it degraded under different irradiation times of the xenon lamp and laser, as well as the Raman spectral changes of the perovskite film under different laser powers, and PL was used for characterization. During the photodegradation process, Raman data and PL spectrum data were collected for at least 6 days from the beginning of irradiation of the organic-inorganic hybrid perovskite film to the 11th day, at least 5 time points per day; for example: 6 days, 5 points per day, a total of 30 data.

[0063] Figure 5a-5f In situ Raman monitoring of the photodegradation process of FACsPbI3 perovskite film under xenon lamp. It can be observed from the figure that when the fresh FACsPbI3 perovskite film is irradiated with 100% laser, a 64.4 cm -1 、91.8cm -1 (hybrid Raman spectrum of perovskite phase), 122.9 cm -1 、140.7cm -1 、142.8cm -1 are laser degradation products, which can be attributed to 122.9 cm -1 (Pb3O4), 140.7cm -1 、142.8cm -1 (PbO) and by Figure 5a It can be seen that there is no difference in the Raman spectra of the newly prepared perovskite film at five time points, proving that the prepared FACsPbI3 perovskite film is relatively stable. It can be observed that the film is still black when placed under a xenon lamp for 3 days. The Raman spectra collected at five time points show that the film has a strong black color at 80.5 cm -1 The Raman peak at 79.9 cm -1 (PbI6 4- The Raman peak at the asymmetric distortion of the octahedral cage is different from that at 64.0 cm -1 、91.8cm -1 The peak position at the bottom of the perovskite was slightly shifted, and the other peaks showed no obvious difference, which indicates that with the continuous irradiation of the xenon lamp, the Cs + It will migrate under the influence of light, resulting in PbI6 4- The octahedral cage is distorted, resulting in partial FA + With the decomposed I- The interaction forms FAI, which is unstable and will be released from the perovskite. After irradiating it under a xenon lamp for 5 days, the film gradually changes from black to reddish brown. The Raman spectra collected at five time points show the Raman peak (91.2 cm) belonging to the perovskite phase. -1 ) completely disappeared, and was replaced by 242.2cm -1 、281.8cm -1 The Raman peaks can be attributed to 242.2 cm -1 (FTO), 281.8cm -1 (PbO), indicating that during the degradation process of the xenon lamp, due to the effect of light intensity on the perovskite structure, its PbI6 4- The octahedral cage is destroyed, and the dissociated Pb reacts with oxygen in the air to generate PbO. Figure 5d-5f It can be observed that when the perovskite is placed under the xenon lamp for 7, 9, and 11 days, the color of the perovskite film gradually becomes lighter and finally turns into light yellow. The Raman spectrum can be observed to appear at 65.2 cm -1 、94.6cm -1 、352.6cm -1 、561.8cm -1 、629.5cm -1 、1100.9cm -1 The Raman peak of 65.2cm -1 、94.6cm -1 The characteristic peak attributed to CsPbI3 is 352.6cm -1 、561.8cm -1 、629.5cm -1 、1100.9cm -1 It is the characteristic Raman peak of FTO. It shows that after 11 days of xenon lamp degradation, the FACsPbI3 perovskite structure has been completely destroyed due to the light intensity. + With the decomposed I - The interaction is released from the perovskite in the form of FAI. + Will be with Pb 2+ ,I - The CsPbI3 perovskite is generated by the action of the catalyst, but due to its low content, the Raman spectrum of FTO is collected. In order to verify this result, the FACsPbI3 perovskite film that was newly prepared, placed under the xenon lamp for 3 days, placed under the xenon lamp for 5 days, placed under the xenon lamp for 7 days, placed under the xenon lamp for 9 days, and placed under the xenon lamp for 11 days was tested by PL, such as Figure 6a-6f shown.

[0064] Depend on Figure 6a-6fIt can be seen that the PL of the newly prepared FACsPbI3 perovskite film is around 793nm. After 5 days of continuous irradiation with a xenon lamp, the PL of the substance was observed to gradually shift to the left. The longer the xenon lamp irradiation time, the more obvious the PL shift of the FACsPbI3 perovskite film, and the intensity of the PL peak decreased significantly. After 11 days of xenon lamp irradiation, the PL of the substance was observed to stabilize at around 699nm. According to the literature, this peak is the characteristic PL peak of CsPbI3. Combined with the previous Raman spectrum, this inference can be further proved to clarify that the photodegradation mechanism of FACsPbI3 perovskite film under 532nm laser is that as the laser power increases, the perovskite degrades into PbO x ; The photodegradation mechanism under xenon lamp is that as the illumination time increases, perovskite degrades into CsPbI3.

[0065] 3. In-situ Raman technology combined with XRD to characterize the thermal degradation mechanism of FACsPbI3 and FAMAPbI3 perovskite films

[0066] In-situ Raman was used to collect Raman spectra of newly prepared FACsPbI3 and FAMAPbI3 perovskite films at different temperatures, and XRD was used to characterize FACsPbI3 and FAMAPbI3 perovskite films at different temperatures. The following figures are Raman spectra of FAMAPbI3 perovskite films collected at least 20 different temperatures (25°C, 35°C, 60°C, 90°C, 120°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 255°C, 280°C, 305°C, 330°C, 355°C, 380°C) between 25°C and 400°C at 1% laser power, as well as the XRD measured at the temperature, as shown in the figure below. Figure 7a-7c , Figure 8a-8b shown.

[0067] from Figure 7a-7c It can be observed that when the temperature rises from room temperature to 120 °C, the Raman peak (64.3 cm -1 、93.8cm -1 ) did not change, indicating that the material was still in the perovskite phase, and then the PbI2 peak gradually appeared at 150℃. When the temperature rose to 170℃, the peak at 71.9cm -1 、93.8cm -1 、108.7cm -1Raman peaks can be observed at 62.0 cm-1, which are very similar to those of PbI2. Therefore, it can be proved that the FAMAPbI3 perovskite film has begun to degrade with the increase of temperature, and its degradation product is PbI2. When the temperature rises to 210°C, it can be observed from the figure that the Raman spectrum characteristic peaks of the film are basically consistent with the characteristic peaks of PbI2, and the crystallinity is getting better and better. However, due to the observation at 62.0 cm-1, the degradation product of the film is PbI2. -1 The Raman peak at 62.0cm indicates that the perovskite film has not only been degraded to PbI2 over a large area, but also has a partial FAMAPbI3 perovskite structure. When the temperature rises to 220 degrees Celsius, the Raman peak at 62.0cm -1 The Raman peak at 140.4cm disappeared, and the intensity of the remaining Raman peaks reached the maximum, indicating that the structure of the perovskite has been completely destroyed and the perovskite film has been completely degraded into PbI2. As the temperature further increases, the intensity of the PbI2 Raman spectrum begins to decrease, and the Raman peak position begins to shift; when the temperature rises to 330°C, the intensity of the Raman characteristic peak of lead iodide is the lowest; when the temperature rises to 330°C, the characteristic peak of the PbI2 Raman spectrum disappears, and a new Raman peak appears; when the temperature rises to 380°C, at 140.4cm -1 A Raman peak appeared at 140.0 cm, which may be the characteristic peak of PbO or polyiodide ion. Subsequently, a PbO diffraction peak was observed in the XRD data, so it was inferred that the 140.0 cm -1 It is PbO instead of polyiodide ions. Here, XRD and Raman spectroscopy are combined to complement and verify each other. The combination of the two can give a clear product identification result.

[0068] XRD was used to characterize the composition of the perovskite films at at least 20 different temperatures between 25°C and 400°C (25°C, 35°C, 60°C, 90°C, 120°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 255°C, 280°C, 305°C, 330°C, 355°C, and 380°C), respectively. Figure 8a-8b As shown. It can be observed from the figure that with the increase of temperature, the intensity of the characteristic diffraction peak of the FAMAPbI3 perovskite film begins to decrease. When the temperature rises to 190°C, the characteristic diffraction peak of the FAMAPbI3 perovskite film disappears, and the characteristic diffraction peaks of PbI2 (11.34°, 12.59°, 38.54°, 52.23°) begin to appear, indicating that the structure of the FAMAPbI3 perovskite is destroyed and gradually degraded into PbI2. When the temperature rises to 210°C, the intensity of the characteristic diffraction peak of PbI2 reaches the maximum, indicating that it has been completely degraded into PbI2 at this time. As the temperature further increases, the characteristic diffraction peak of PbI2 begins to disappear. At 305°C, the FAMAPbI3 perovskite film shows PbO at 28.57°. xWhen the temperature rises to 355℃, PbO x The characteristic diffraction peak of PbO is 29.45°; when the temperature rises to 380°C, x The characteristic diffraction peak of PbI2 is 30.51°. The above results show that the increase in temperature causes PbI2 to further degrade and combine with oxygen in the air to form PbO x This is basically consistent with the spectral characteristic peaks obtained by in-situ Raman monitoring of perovskite films. It can be determined that the thermal degradation mechanism of perovskite films is that as the temperature increases, perovskite first degrades to PbI2 and then to PbO x .

[0069] The present invention utilizes in-situ Raman spectroscopy technology in combination with PL and XRD to perform in-situ monitoring on the degradation process of FACsPbI3 and FAMAPbI3 perovskite films, studies the phase transition and the interaction between ions and vacancies during light and / or thermal degradation, and thus analyzes the light and / or thermal degradation mechanism.

[0070] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0071] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. An in-situ monitoring method for the photo- and / or thermal degradation mechanism of an organic-inorganic hybrid perovskite film, characterized in that: include: The organic-inorganic hybrid perovskite film is subjected to thermal degradation and / or photodegradation, and Raman data and XRD diffraction peak data of the organic-inorganic hybrid perovskite film during the thermal degradation process are collected using Raman and XRD combined technology; and / or, Raman data and PL spectrum data of the organic-inorganic hybrid perovskite film during the photodegradation process are collected using Raman and PL spectrum technology; The acquired data are analyzed and processed to realize in-situ nondestructive monitoring of the photo and / or thermal degradation of organic-inorganic hybrid perovskite films.

2. The in-situ monitoring method according to claim 1, characterized in that: Specifically include: The organic-inorganic hybrid perovskite film was heat treated by a hot stage, and the Raman data and XRD diffraction peak data of the organic-inorganic hybrid perovskite film at different temperatures were collected by using Raman and XRD combined technology; The obtained Raman data and XRD diffraction peak data are analyzed and processed to clarify the phase changes, the interaction between ions and vacancies and their changing laws during the thermal degradation of organic-inorganic hybrid perovskite films.

3. The in-situ monitoring method according to claim 2, characterized in that: The Raman data and XRD diffraction peak data of the organic-inorganic hybrid perovskite film at at least 3 different temperatures between 25°C and 400°C are collected.

4. The in-situ monitoring method according to claim 2, characterized in that: The organic-inorganic hybrid perovskite film may undergo changes in crystal structure during thermal degradation.

5. The in-situ monitoring method according to claim 2, characterized in that: When the organic-inorganic hybrid perovskite film is a FAMAPbI3 perovskite film, the FAMAPbI3 perovskite structure is destroyed during the thermal degradation process, and MAI and FAI are released from the structure in sequence, so that the main component of the degradation product is PbI2; then PbI2 decomposes as the temperature rises, I- is released from the structure in the form of iodine, and the Pb remaining in the structure combines with O2 in the air to form PbO x Remain on the FTO surface.

6. The in-situ monitoring method according to claim 1, characterized in that: Specifically include: The organic-inorganic hybrid perovskite film is irradiated with a xenon lamp or laser to simulate photodegradation, and the Raman data and PL spectrum data of the organic-inorganic hybrid perovskite film under different illumination times are collected using Raman and PL spectrum techniques; The obtained Raman data and PL spectrum data are analyzed and processed to clarify the phase changes, the interaction between ions and vacancies and their changing laws during the photodegradation of organic-inorganic hybrid perovskite films.

7. The in-situ monitoring method according to claim 6, characterized in that: Raman data and PL spectrum data were collected for at least 3 days from the start of irradiation of the organic-inorganic hybrid perovskite film to the 11th day.

8. The in-situ monitoring method according to claim 6, characterized in that: When the organic-inorganic hybrid perovskite film is a FACsPbI3 perovskite film, during the photodegradation process, FA + Will first with PbI6 4- The interaction forms FAI, which is then completely released from the film, while CsPbI3 is formed in the film during the photodegradation process.

9. The in-situ monitoring method according to claim 6, characterized in that: The wavelength used by the laser is selected from 532nm, 633nm, 785nm or 1064nm.

10. The in-situ monitoring method according to claim 1, characterized in that: The organic-inorganic hybrid perovskite film includes a FACsPbI3 perovskite film and / or a FAMAPbI3 perovskite film.